2012
DOI: 10.14710/ijred.1.3.115-122
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Production of Karanja Oil Methyl Ester and Its Effect on Diesel Engine

Abstract: Fast depletion of fossil fuel resources forces the extensive research on the alternative fuels. Vegetable oils edible or non edible can be a better substitute for the petroleum diesel. Karanja, a non edible oil can be a potential source to replace the diesel fuel. To investigate the feasibility of Karanja oil as an alternative diesel fuel, its biodiesel was prepared through the transesterification process. The Biodiesel was then subjected to performance and emission tests in order to assess its actual performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…It was found that B100 KOME biodiesel reduces about 73-94% CO emission [66]. Besides, [52,87,89] agreed that KOME biodiesel reduces the CO emission as illustrated in Figure 8 [52]. Numerous studies also showed that biodiesel reduces PM emission in CI engine [62-69, 80-83, 85, 94, 95, 101-107, 119-123].…”
Section: Engine Performance and Emission Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…It was found that B100 KOME biodiesel reduces about 73-94% CO emission [66]. Besides, [52,87,89] agreed that KOME biodiesel reduces the CO emission as illustrated in Figure 8 [52]. Numerous studies also showed that biodiesel reduces PM emission in CI engine [62-69, 80-83, 85, 94, 95, 101-107, 119-123].…”
Section: Engine Performance and Emission Analysismentioning
confidence: 98%
“…However, astonishing power increase due to use of pure biodiesel was noticed by [85,86]. Karanja methyl ester (KOME) B100 which reduces the brake thermal efficiency of CI engine was investigated by some researcher [87,88]. Minor difference between the engine efficiency of using KOME and pure diesel was found in [89,90].…”
Section: Engine Performance and Emission Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Transesterification is a reversible reaction between triglyceride and alcohol in presence of catalyst to produce glycerol and mono alkyl ester which is known as biodiesel [9,10]. Weight of the mono alkyl ester is one third of that of typical oil and therefore has lower viscosity.…”
Section: Transesterification Reactionmentioning
confidence: 99%
“…Alkali (NaOH, KOH), acid (H 2 SO 4 , HCL) or enzymes (lipase) catalyzed reaction. Acid catalyzed transesterification is most commonly used process because it is a reversible reaction [10]. In the transesterification process methanol and ethanol are more common.…”
Section: Transesterification Reactionmentioning
confidence: 99%